2009
DOI: 10.5551/jat.943
|View full text |Cite
|
Sign up to set email alerts
|

Possible Association of Atrophic Gastritis and Arterial Stiffness in Healthy Middle-Aged Japanese

Abstract: Aim: Helicobacter pylori (HP) has been implicated as a risk factor for cardiovascular and atherosclerotic diseases. Arterial stiffness determined by pulse wave velocity (PWV) or the cardio-ankle vascular index (CAVI) has been shown to be higher in HP-positive subjects than in HP-negative subjects; however, this result has been observed only in young subjects. The aim of the study was to investigate the possible correlation between HP infection and PWV or CAVI in middle-aged subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 43 publications
1
20
0
1
Order By: Relevance
“…Although the relationship between H. pylori status and adiponectin has not been reported yet, there is one recent report on the circulating levels of adiponectin in patients with atrophic gastritis, in which the cause in most cases was H. pylori infection . Torisu et al.…”
Section: Discussionmentioning
confidence: 99%
“…Although the relationship between H. pylori status and adiponectin has not been reported yet, there is one recent report on the circulating levels of adiponectin in patients with atrophic gastritis, in which the cause in most cases was H. pylori infection . Torisu et al.…”
Section: Discussionmentioning
confidence: 99%
“…Torisu et al 67) reported that CAVI was significantly higher in atrophic gastritis-positive patients than in atrophic gastritis-negative patients, even after adjusting for possible confounding factors (8.59 1.20 vs. 8.27 1.19 p 0.022).…”
Section: H Miscellaneous Diseases And/or Conditionsmentioning
confidence: 99%
“…Pulse wave velocity, carotid IMT and FMD were not different in patients with AIG who were negative and positive for H. pylori infection. Torisu et al compared 210 H. pylori positive patients with 133 H. pylori negative patients in terms of PWV [38]. However, they did not find an association between PWV changes and H. pylori status.…”
Section: Discussionmentioning
confidence: 96%